Idiopathic Chronic Eosinophilic Pneumonia: A Rare Condition - Huma Firdaus; shadan sadaf; Maqsumi Reza (International Journal of Pharma and Bio Sciences, 2023)
Respirational and universal indications that be chronic or acute, blood and alveolar eosinophilia, and distal respiratory infiltrates on chest imaging describe idiopathic-chronic-eosinophilic-pneumonia (ICEPn). Most individuals have eosinophilia, which is generally more than 1000/mm3. The lack of substantial blood eosinophilia syndrome reinforces an identification of ICEPn. Eosinophilia in the Bronchoa-Alveolar-Lavage(BrAL) is usually linked with elevated eosinophil levels. ICEPn is an uncommon condition with an unknown origin. Its precise prevalence needs to be clarified. ICEPn can affect anybody at any age, although it is more common in children. It affects women twice as much as males. Asthma affects one-third to one-half of all ICEPn patients. Systemic corticosteroids are the source of ICEPn therapy. Outlying blood eosinophilia may be evident during the initial case presentation, but it might be missing or delayed, particularly in smoking-related AEPn. Our review is focused on ICEPn, Lung Diseases, Chest Imaging, Pathogenesis, and Pathology. The basis of treating AEPn of non-infectious etiology is the termination of exposure to the inciting substance (e.g., smoking) and glucocorticoids. If AEPn is identified and treated promptly, the prognosis is typically favorable, with early and full clinical recovery.